Toward Data Protection laws and code of conduct in Kurdistan region government (International Journal of Engineering and Computer Science, 2015)
Kurdistan Region Government is a s a developing region in Iraq. Since 1992, Kurdistan parliament has reported numerous standards and regulation in diverse ranges aside from Information advances and PC set of accepted rules laws. KRG has separated from Iraq influenced by hacking their touchy data and digital unlawful acts since war 2003. In Kurdistan Region there are numerous web gives the vast majority of them upheld by private segment and they don't have any significant bearing PC laws and set of accepted rules to keep the costumers from information lost, protection rupture and digital law violations. This paper will examine every one of the cases related PC law break in broad daylight and private divisions of KRG (Kurdistan Region Goverment) organizations. The study will propose a standard guidelines and regulation for all web suppliers keeping in mind the end goal to minimize hacking and digital law violations. Moreover, of that the examination will propose the how it can apply the PC laws and regulation and the results of abusing these laws for individual and establishments. This study due of development private sectors and there are many Internet providers In Iraq and KRG without clear law to apply for all providers regarding data privacy and protections. There are numerous cases in Iraq and Kurdistan Region Government identified with Information Technology This paper will overview law experts and mastery in laws. This will bolster the lawful prerequisites required for applying the PC Law in KRGs governments.